Beliefs about others' global warming beliefs: The role of party affiliation and opinion deviance. (August 2020) - Ballew, Matthew T.; Rosenthal, Seth A.; Goldberg, Matthew H.; Gustafson, Abel; Kotcher, John E.; Maibach, Edward W.; Leiserowitz, Anthony
Abstract: People often misperceive other people's beliefs about global warming—for instance, underestimating the percentage of people who think global warming is happening. In the U.S., perceptions of others vary across political lines and interact with the extent to which partisans align or deviate from the views of their political ingroup. With an online sample of U.S. adults ( N  = 1214), we conduct a partial replication and extension of prior research on the relationship between global warming "opinion deviance" (i.e., taking a stance that conflicts with the prototypical views of one's ingroup) and perceptions of other people's views, using a different methodological approach. We found that, compared with partisans who align with the prototypical views of their ingroup (i.e., political party), opinion-deviant partisans consistently perceive a narrower partisan divide across several views (e.g., belief that global warming is happening, belief that it is human-caused, and support for climate policies), even when statistically controlling for self-reported opinion extremity. Additionally, opinion-deviant Republicans, more than opinion-aligned Republicans, perceive that more Republicans hold pro-climate views. Further, among both Republicans and Democrats, perceptions of pro-climate ingroup consensus correlates with both increased activism intentions and frequency of discussing global warming with family and friends. Our results support theoretical perspectives and research on opinion deviance showing that misperceptions of public opinion about global warming vary based on an interaction between an individual's party affiliation and their individual climate beliefs. Highlights: Opinion deviants hold views that conflict with the prototypical views of ingroups. Findings replicate previous research on the effects of opinion deviance. Opinion deviants perceive a smaller partisan gap in global warming views. Opinion-deviant Republicans perceive that Republicans hold more pro-climate views. Perceived social consensus correlates with climate activism intentions.